Предмет: Алгебра,
автор: rightgamesfy
1) 3(x - 4) = x; 3) 5(x - 2) = 2x; 5) 3(-x - 1) = -(2x + 3);
Ответы
Автор ответа:
0
1) 3(x - 4) = x
3х - 12 = х
3х - х = 12
2х = 12
х = 6
Ответ: 6
3) 5(x - 2) = 2x
5х - 10 = 2х
5х - 2х = 10
3х = 10
х = 3
Ответ: 3
5) 3(-x - 1) = -(2x + 3)
-3х - 3 = -2х - 3
-3х + 2х = -3 + 3
1х = 0
х = 0
Ответ: 0
Автор ответа:
2
1)
3(x - 4) = x
3х-3×4
3х-12
3х-12=х
3х=х+12
2х=12
2х÷2=12÷2
х=12÷2
х=6
2)
5(x - 2) = 2x
5х-10=2х
5х=2х+10
5х-2х=10
3х=10
3х÷3=10÷3
х=10÷3
х=3,3
3)
3(-x - 1) = -(2x + 3)
-3х-3=-(2х+3)
-3х-3=-2х-3
-3х=-2х
-3х+2х=0
(-3+2)х
-1х
х=0
Похожие вопросы
Предмет: Музыка,
автор: katazura140708
Предмет: Английский язык,
автор: mashaopalehyk09
Предмет: Математика,
автор: Kamol2906
Предмет: Информатика,
автор: BartMan228
Предмет: Математика,
автор: ti1511